1983
DOI: 10.1128/aac.23.3.429
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of cefoperazone, cefotaxime, and moxalactam

Abstract: The pharmacokinetics of cefoperazone, cefotaxime, and moxalactam were compared in a cross-over randomized study in 10 healthy volunteers. Each subject received 1.0 g of the three drugs by bolus intravenous injection over 3 min. Serum and urine concentrations were assayed by a microbiological method and in addition by high-pressure liquid chromatography (HPLC) for cefotaxime in five subjects. Maximal concentrations in serum 5 min after the injection were 163 ± 40.3 mg/liter for cefoperazone, 86.1 ± 19.0 mg/lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The First Order Conditional Estimation with interaction (FOCEI) method was employed throughout the analysis. As has been previously reported, we observed that the pharmacokinetic data were best fit by a two‐compartment model 20,38,39. Cefotaxime clearance was parameterized using the Eqs.…”
Section: Resultsmentioning
confidence: 80%
“…The First Order Conditional Estimation with interaction (FOCEI) method was employed throughout the analysis. As has been previously reported, we observed that the pharmacokinetic data were best fit by a two‐compartment model 20,38,39. Cefotaxime clearance was parameterized using the Eqs.…”
Section: Resultsmentioning
confidence: 80%
“…Data from preclinical and clinical trials reported differences in ceftriaxone and cefotaxime pharmacokinetic characteristics, in particular, differences in their biliary elimination. The proportion of administered ceftriaxone excreted by bile after each dose has been estimated to be approximately 40% (13,14), which is 4 times higher than that of cefotaxime (15,16). In their animal study, van Ogtrop and colleagues treated mice with either cefoperazone, ceftriaxone, cefepime, or ceftazidime, whose intestinal elimination ranges from 0.2% to 37% of the administered dose (17).…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen antimicrobial agents were chosen, based on their recommended use for therapy or prophylaxis of meningococcal infections. PK-PD parameters, protein binding, and the variability of these measurements, were obtained from the published literature for ampicillin, azithromycin, cefotaxime, ceftriaxone, chloramphenicol, ciprofloxacin, doxycycline, levofloxacin, meropenem, minocycline, penicillin G, rifampicin, sulphafurazole, tetracycline and trimethoprim-sulphamethoxazole (Table 1) [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Data concerning penetration into the cerebrospinal fluid (CSF) were also obtained from the literature [22][23][24].…”
Section: Antimicrobial Agentsmentioning
confidence: 99%